Nasal Myiasis: Clinical Insights from a Case Report - Manish Kumar Mandal; Sumit Kumar Jha; Rishi Raj Sah (Janaki Medical College Journal of Medical Science, 2025)
Background and objectives: Nasal myiasis is a rare parasitic infestation of the nasal cavity by dipteran fly larvae, often associated with poor hygiene, low socioeconomic status, or comorbidities, and is often neglected. Presentation of the case: This case report highlights an unusual presentation of nasal myiasis in a middle-aged, well-educated individual with good personal hygiene and no significant predisposing factors in Dhanusha of Madhesh Province. Primary examination revealed increased blood pressure and epistaxis. Discussion: Primary radiological findings are multiple round-oval hypodense areas in the right nasal cavity and in the nasopharynx near the opening of the left Eustachian tube. The aim is to underline the importance of early diagnosis, prompt treatment, and public awareness to prevent complications. Conclusion: The early diagnosis of myiasis can overcome complications such as basal skull invasion, blindness, invaded meninges, and, in severe cases, death can be prevented. Understanding the feat, it can be treated even in a hospital setting with fewer resources.